2012
DOI: 10.1016/j.bbrc.2012.09.144
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interferon-beta mRNA stability control after poly(I:C) stimulation using RNA metabolic labeling by ethynyluridine

Abstract: Interferon-beta (IFN-β) is a critical antiviral cytokine and is essential for innate and acquired immune responses to pathogens. Treatment with polyinosinic:polycytidylic acid (poly(I:C)) induces transient accumulation of IFN-β mRNA, which involves an increase and a decrease of IFN-β mRNA. This phenomenon has been extensively analyzed as a model for understanding the mechanisms of gene induction in response to external stimuli. Using a new RNA metabolic labeling method with ethynyluridine to directly measure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Consistent with this result we observed induction of endogenous ISG56, IFN-β and type III IFN expression upon SeV infection and these responses barely differed between the MAVS variants ( Fig 3C ). As reported earlier [ 43 , 44 ], IFN-β expression was rapidly and very transiently induced and this also applied to IFN-λ1. In contrast, activation of IFN-λ2/3 expression was much more sustained and did not decline throughout the 48 h observation period.…”
Section: Resultssupporting
confidence: 73%
“…Consistent with this result we observed induction of endogenous ISG56, IFN-β and type III IFN expression upon SeV infection and these responses barely differed between the MAVS variants ( Fig 3C ). As reported earlier [ 43 , 44 ], IFN-β expression was rapidly and very transiently induced and this also applied to IFN-λ1. In contrast, activation of IFN-λ2/3 expression was much more sustained and did not decline throughout the 48 h observation period.…”
Section: Resultssupporting
confidence: 73%
“…We suspect that BrU is not effectively incorporated into serum-starved cells. Instead, we used another inhibitor-free method, 5-Ethynyluridine (EU) pulse-labeling, which is commercially available as the Click-iT Nascent RNA Capture Kit (Invitrogen) [33][36]. We have successfully determined the half-life of GAS5 with or without serum starvation by the EU method, and found that t 1/2 of GAS5 was prolonged from 4.2 h to >12 h in serum starved cells (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of RNA half-lives was performed by EU pulse-labeling of RNA using the Click-iT Nascent RNA Capture Kit (Invitrogen) [33][36]. After serum withdrawal for 24 h, 200 µM of EU was added to medium and cells incubated for an additional 24 h. At indicated time points after replacing EU-containing medium with EU-free medium, cells were harvested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that other nucleoside analogs can be used for metabolic labeling and half-life determination including 5-bromouridine (5BrU) [3336] and 5-ethynyluridine (5EU) [37]. The approach described here could be adapted to these nucleosides simply by replacing the positive control RNA with one labeled with 5EU or 5BrU and following established protocols for labeling and fractionation.…”
Section: Introductionmentioning
confidence: 99%